Ketahanan Bisnis Perkeretaapian di Masa Pandemi COVID - 19 - Kurniawan, Dwi Ardianta (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2021)
The COVID-19 pandemic has resulted in decreasing on volume and revenue railway passenger in Indonesia by around 53%, while freight transport has decreased by about 5% compared to 2019. Policies that can be implemented to overcome the impact of a pandemic include Operational Optimization based on operating efficiency, and Pandemic Adaptation based on minimizing 3C conditions. (Closed Space, Crowded Place, Closed Contact Setting). The impact of implementing the policy needs to be simulated its effect on operating costs (BO) and operating income (PO). The results of the comparison of PO and BO values, hereinafter referred to as POBO, are an indicator of how strong the railway business is able to survive during a pandemic. A POBO value above 1.0 indicates that the business is still able to reach the Break Event Point (BEP), which means that the operator is able to achieve revenue equivalent to costs (fixed and variable). The critical point of railway operation occurs at the shutdown point, which indicates that revenue cannot cover fixed costs. At the shutdown point, it is feared that the railway business will stop. The calculation results show that the POBO values of the two policies are 1.08 (optimization policy) and 1.09 (pandemic adaptation policy). This profile shows the resilience of the railroad business at the threshold value of the Break Event Point (BEP), far below the POBO value in previous years. This shows that the impact of the pandemic is very significant on the company's cash flow. The critical point for the shutdown point occurred in the volume of goods and passengers by up to 40% compared to the volume in 2019. This volume was lower than the basic calculation, namely passenger volume of 50.5% - 55.5%; and the volume of goods by 81.5% compared to the volume in 2019. This figure shows that the railroad business still has resilience before experiencing a critical shutdown point.